Zero product rule

The zero product rule states that
If the product of two or more expressions is zero, then either expression is equal to zero.
For example, if `a * b = 0`, then either `a = 0` or `b = 0`.

The zero product rule is used to solve quadratic equations when you have factored them. An example is as follows:

The quadratic equation
`x^2 + 3x + 2 = 0`
is factored into
`(x + 1)(x + 2) = 0`
Applying the zero product rule,
either `x + 1 = 0`, then `x = -1`
or `x + 2 = 0`, then `x = -2`
Therefore we obtained the solution `x = {-1, -2}` for the quadratic equation `x^2 + 3x + 2 = 0` by using the Zero Product Rule.

No comments:

Post a Comment

Search This Blog